ANALISIS NILAI TAMBAH KEDELAI SEBAGAI BAHAN BAKU USAHA TAHU TEMPE SUTIKNO DI KELURAHAN BATU KOTA BAWAH KECAMATAN MALALAYANG KOTA MANADO (Analysis Of Additional Value Of Soybean As A Raw Material For Tempe and Tofu Processing (Case Study: Business Tofu Tempe Pak Sutikno In Batu Kota Bawah Kelurahan Malalayang Sub District Manado City) - Kharis Swingly Kaela; Eyverson Ruauw; Tommy F. Lolowang (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2021)
The purpose of this research is to analyze the added value and advantages of processing soybeans into tempe and tofu. This research was conducted for 3 months from September to November 2019 in Pak Sutikno's Tempe Tofu Industry in the Sub-District of Batukota Bawah Kelurahan , Malalayang Sub District, Manado City. The data used includes primary data obtained by interviewing business owners. Data analysis from the data used is added valueÂ and profit analysis.The research results showed that Pak Sutikno's tofu business resulted in added value of soybeans to tempe in a month of production amounting to Rp. 21,676,533 and the added value in one production time is Rp. 722.55 and the added value in 1 kg of raw materials is Rp. 9,032. The added value generated from processing soybeans into tofu is Rp. 101,399,733 in a month of production and as much as Rp. 3,379,991 in one time production and Rp. 12,426 in one kilo gram of raw material is Rp. 12,426. The profit generated from processing soybeans into tempeh is Rp. 160,885 in one time and Rp. 4,826,550. in one month of production, and the profit generated from processing soybeans into tofu is Rp. 2,818,325 in one production and Rp. 84,549,750 in one month of production.Keywords: added value, profit, soybean, tofu, tempe